2012
DOI: 10.1177/0040517512436827
|View full text |Cite
|
Sign up to set email alerts
|

Does quilting improve the fragment protective performance of body armour?

Abstract: The primary function of military body armour is to provide protection from fragmenting munitions and improvised explosive devices (IEDs). This is usually achieved by the use of multiple layers of woven para-aramid fabric. The resulting body armour is heavy and contributes to the burden on the dismounted soldier. Reduction in body armour mass and hence thermophysiological loading without reducing the level of protection is therefore of interest worldwide. Many manufacturers quilt the fabric component of body ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…The weave of the fabric provides the similar interactions as the lateral crosslinking in mammalian dermis while the quilt-stitching replicates at least a portion of the transverse linkages. In fact, quilt-stitching was shown to increase the energy absorption in fragment impacts 14%-22% over non-quilted armours [54].…”
Section: Soft Engineered Armourmentioning
confidence: 99%
“…The weave of the fabric provides the similar interactions as the lateral crosslinking in mammalian dermis while the quilt-stitching replicates at least a portion of the transverse linkages. In fact, quilt-stitching was shown to increase the energy absorption in fragment impacts 14%-22% over non-quilted armours [54].…”
Section: Soft Engineered Armourmentioning
confidence: 99%
“…The purpose of the soft component of military body armour is to defeat explosively propelled fragments or to significantly reduce their energy to minimise wounding potential. 5 Unlike body armour issued to police officers, stab resistance and low-velocity hand gun bullets are not threats which military soft body armour is designed to defeat. Soft body armour is composed of multiple components, of which the ballistic protective fabric is only a part of ( Table 1).…”
Section: Components Of Soft Body Armourmentioning
confidence: 99%
“…The performance of soft armour is typically measured using steel fragment simulating projectiles (FSPs). 5 The most commonly used FSP remains the 1.10 g chisel-nosed cylinder (Figure 2), which was originally based on fragment masses produced from a 155 mm artillery shell; however, it has been shown to represent the heterogenous shapes of fragments found in improvised explosive devices (IEDs). Steel spheres are commonly found in preformed fragmenting munitions; research suggests that these should also be used for testing as this shape of fragments has been demonstrated in significant proportions in UK soldiers sustaining neck wounds from explosively propelled fragments.…”
Section: Ballistic Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The diamond stitched pattern has better movement of fabric control and hence higher puncture resistance properties than other stitching patterns. Carr DJ [7] found that the amount of energy absorbed during ballistic impacts for diamond quilted was 14% and 22% higher compared to non-quilted and square quilted depending on the number of fabric layers.…”
Section: Introductionmentioning
confidence: 99%